When crime hits communities: A story of fear and depression in Mexico - Esther Heesemann; Slava Yakubenko (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Illegal activities harm individuals and society as a whole. Besides the physical harm and immediate wealth loss, crime can entail more subtle, long-lasting consequences, namely, impaired mental health. This article presents significant evidence that the surge of crime rates in Mexico contributed to higher incidence of major depressive disorder in the population. Focusing on Mexico allows us to analyse how a sudden, arguable exogenous shock on overall crime rates in the 2000s, namely the initiation of the war on drugs, affects the incidence of depression. We take advantage of the micro-level panel data to establish several channels through which crime provokes depression of victims and their surrounding: (1) acute stress from being the victim; (2) long-term stress due to low safety perception; (3) destruction of social capital in communities exposed to high crime rates. These findings document less immediate consequences of conflict and have to be accounted for designing an efficient mental health policy.
Keywords: I10; I18; D91; 330; depression; crime; mental health; Mexico